Plataformas interactivas y su incidencia en el aprendizaje de los estudiantes de 6to año EGB de la U.E Emigdio Esparza Moreno, 2024 – 2025 - Jiménez Rodríguez, Wendy Jessenia (2025)
Interactive platforms are digital tools that allow an active interaction between students and educational content, facilitating their learning through dynamic activities, multimedia resources and instant feedback, these platforms promote a more participatory and motivating educational environment, which favors the acquisition of knowledge in an autonomous and personalized way. The objective of this research is to determine the incidence of interactive platforms in the learning of 6th grade EGB students of the Emigdio Esparza Moreno Educational Unit during the period 2024-2025. The population and sample are made up of 1 teacher and 33 students of 6th grade EGB “D”. The methodology used is a mixed approach, with a descriptive, field and documentary design, and a non-experimental design. For data collection, surveys with closed-ended questions to students and interviews with open-ended questions to teachers will be used. This study seeks to analyze how the use of interactive platforms affects the academic performance, motivation and participation of students, since, being digital tools, they allow fostering a dynamic and personalized environment that improves understanding, motivates students and promotes their active participation, which contributes to better academic performance.